2021
DOI: 10.1002/ddr.21790
|View full text |Cite
|
Sign up to set email alerts
|

Protection of clozapine‐induced oxidative stress and mitochondrial dysfunction by kaempferol in rat cardiomyocytes

Abstract: Clozapine (CLZ) is unusually efficient in psychotic diseases. Nonetheless, its use is confined due to potentially life-threatening adverse events, including cardiotoxicity.Since the cardiotoxicity of CLZ is mediated through the generation of active metabolites, free radical, and inflammation. Here, we tested this hypothesis that kaempferol (KP) as antioxidant and anti-inflammatory agent could attenuate CLZ-induced mitochondrial/lysosomal and oxidative damages in rat ventricular cardiomyocytes. Rat ventricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…This suggested that lower concentrations of KPR (up to 100 μM) did not impair the cellular integrity, while the 200 μM concentration induced toxicity, as evidenced by increased LDH release into the cell culture medium. Therefore, combined with the previous studies (Al Sabaani, 2020; Bakhshii et al., 2021; Kim et al., 2016), 50 μM KPR was selected as the optimal concentration for the following experiments.…”
Section: Resultsmentioning
confidence: 99%
“…This suggested that lower concentrations of KPR (up to 100 μM) did not impair the cellular integrity, while the 200 μM concentration induced toxicity, as evidenced by increased LDH release into the cell culture medium. Therefore, combined with the previous studies (Al Sabaani, 2020; Bakhshii et al., 2021; Kim et al., 2016), 50 μM KPR was selected as the optimal concentration for the following experiments.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, quercetin and kaempferol protected testicular SCs from oxidative stress injury and improved their resistance to heat stress, which was consistent with previous studies [ 61 , 62 ]. Quercetin and kaempferol have a weak ability to improve SOD activity of heat-damaged supporting cells, but for flavonoid monomers, their antioxidant ability lies not only in improving the level of antioxidants, such as SOD but also in their unique active structure to prevent and eliminate oxygen free radicals [ 63 , 64 ]. Quercetin has one more ortho phenolic hydroxyl than kaempferol.…”
Section: Discussionmentioning
confidence: 99%
“…8, Table 7). Pharmacological studies indicated that these compounds, particularly kaempferol and its derivative, had a wide range of biological activities including antiproliferation, antioxidation, anti-inflammation, anticancer, anti-free radical, and neuroprotection activities [96][97][98][99] 8). They were isolated from this plant for the first time [108].…”
Section: Flavones Isoflavones and Flavonolsmentioning
confidence: 99%
“… 155 7,4′-Dihydroxyflavone A. chinensis Planch [ 105 ] Roots Anti-inflammatory (in vitro) [ 106 ] 156 Formononetin A. chinensis Planch [ 105 ] Roots 157 Kaempferol A . deliciosa [ 107 ] Leaves Antiproliferation human tumor cell (in vitro) [ 96 ] Antioxidant and anti-inflammatory (in vitro) [ 97 ] Anticancer (in vitro) [ 98 ] Neuroprotection (in vitro) [ 99 ] 158 6-C-Glucose-5,7,3′,4′-tetrahydroxy flavone A. arguta [ 108 ] Roots 159 6-C-Glucose-5,7,4′-trihydroxy flavone A. arguta [ 108 ] Roots 160 6-C-Glycopyranosyl-8-C-xyloeyl apigenin A. polygama [ 109 ] Leaves 161 Vicenin-I A. polygama [ 110 ] Aerial Parts 162 Kaempferol 3-O-glucoside A . deliciosa [ 107 ] Leaves 163 …”
Section: Chemical Constituentsmentioning
confidence: 99%